UPAYA PEMBERDAYAAN PEREMPUAN DALAM PENGELOLAAN TANAMAN TOGA DI DESA TULUNG SELAPAN TIMUR - Kencana, Tarisa Dwi (PRAJA: Jurnal Ilmiah Pemerintahan, 2024)
The purpose of this study was to find out how the village government's strategy in empowering village communities towards Toga Plant Management in East Tulung Selapan Village. This study uses a qualitative approach that aims to understand symptoms that do not require quantification. The subjects of the study were the Head of East Tulung Selapan Village, the Head of the East Tulung Selapan Village PKK, the East Tulung Selapan Village PKK Member, the management of TOGA plants in East Tulung Selapan Village, namely Observation, Interview, and Documentation. The data analysis used refers to the stages described by Miles and Huberman which consist of three stages, namely: data reduction, data presentation (and conclusion drawing or verification or commonly known as interactive analysis mode. This Toga plant program has been running since the existence of the central government. In terms of the implementation of the Toga plant program, it has been supported by the community, especially in Tulung Selapan Timur Village and many improvements are still needed such as training on the use of toga and assistance in toga plant processing machine technology. This improvement is needed to support community empowerment in Tulung Selapan Timur Village, especially housewives. This family medicinal plant program can increase the productivity of housewives, besides that it can also improve the economy of the community in East Tulung Selapan Village, especially housewives.